Influence of ambient water intrusion on coral reef acidification in the Chuuk lagoon, located in the coral‐rich western Pacific Ocean. Issue 8 (25th April 2016) - Ko, Young Ho; Lee, Kitack; Noh, Jae Hoon; Lee, Charity M.; Kleypas, Joan A.; Jeong, Hae Jin; Kim, Kwang Young
Abstract: Weekly carbonate chemistry condition data recorded between 2008 and 2014 in the Chuuk lagoon (7.3°N and 151.5°E) of the Federated States of Micronesia, located in the western Pacific Ocean, were analyzed. The results showed that, during periods of weak intrusion of ambient seawater from the surrounding open ocean, two internal biological processes (calcification and respiration) reinforced each other and together lowered the pH of the reef water for extended periods, ranging from a few to several months. The analysis indicated that reduced intrusion of ambient water is associated with periods of low wind speeds. Such conditions increase the residence time of reef water, thus promoting acidification by respiration and calcification. This phenomenon likely affects many other areas of the coral‐rich western Pacific Ocean, which contains 50% of global coral reefs and in which the degree of ambient water intrusion into the atolls has been shown to be closely associated with the El Niño–Southern Oscillation‐induced wind speed change. Key Points: We analyzed carbonate chemistry measurements, recorded weekly between 2008 and 2014 in the Chuuk lagoon in the western Pacific Ocean Under the longer water residence time conditions, calcification and respiration together lowered the pH of the reef water A strong link was found between reef water carbonate chemistry and large‐scale climatic variations